Microstructure and mechanical properties of magnetron sputtered Ti-Si-N coatings with different silicon content - Dergham, Driss; Chekour, Lounis; Khen, Adel (Malaysian Journal of Science, 2017)
This work deals with the deposition and characterization of (Ti-Si-N) coatings. A series of Ti-Si-N thin films with different silicon content were deposited on Si (100) substrate by RF magnetron sputtering in an Ar-N2 gas mixture. The influence of Si content on the microstructural and mechanical properties of the as deposited. The as deposited films were studied by using different characterization techniques such as SEM equipped with Energy Dispersive X-ray spectroscopy (EDS) for determining the composition of the films, XRD was used to determine microstructural composition and nano-indentation with MTS XP system for mechanical properties. Scherer’s formula was used to determine the grain size, from the full width at half maximum of (111) experimental peaks, residual stresses of the films were measured by an optical interference apparatus using Newton’s ring method Results reveal that the film deposited with Si content of 20 at. % has a dense nanostructure and the surface morphology of the Ti-Si-N coatings show neither holes nor column headings. The film deposited with Si content of 33 at. % shows a surface morphology of damaged surface. The X-ray spectra show that Ti-Si-N coatings deposited with Si content of 0 at.%, 27 at.%, 33 at.%, 40 at.% possess a preferential orientation in the direction of (111) and this orientation peak disappears for films with low of Si content. The residual stress built in the coating is compressive and they increase with increase in Si content and reach a maximum of 2.22 GPa. The hardness of the Ti-Si-N films also increases to a maximum with increase in Si content beyond which further addition of the Si decrease the hardness. The TiN grain size as calculated from the XRD diffraction peak decreases with increase in the Si content to saturation value of around 12.8nm for films without addition of silicon to 3.8nm for films with 40at. % of Si Keywords: hard coating, magnetron sputtering, residual stress; grain size, Ti-Si-N